Lecturer Committee Management System - Mohamed, Hasiah; Nor Adzmi, Nurul Husna Amalina (International Journal of Advanced Science Computing and Engineering, 2019)
Teaching is the main task of the lecturer besides research, consultancy and holding administrative post. Administrative post consist of post that need to be held for either two (2) years or 1 year depending on the job scope. Currently, there are difficulties in assign post to lecturer. Beside, it is time consuming to trace the current post of lecturer. In order to solve the current process, a system known as Lecturer Committee Management System (LCMS) is proposed. LCMS can be used to propose and assign post to lecturer and to track lecturer involvement history in committee. The method use in the development of LCMS is Rapid Application Development (RAD) model. Once the development process completed, expert evaluation and user evaluation have been conducted. For the expert there are a few question that have been asked in order to improve the usability and functionality of the LCMS. For the user, there are six construct provided in order to evaluate LCMS. The result show that respondents agree LCMS is easy to use with the highest mean is 4 (SD=0.41). Lastly, as for the future enhancement new features such as lecturer can get the notification about post assigned via phone.